INVERSI LINIER LEASTSQUARE DENGAN MATLAB ( Studi Kasus Model Gravitasi Bola Berlapis) - Nurwidyanto, Irham; Setiawan, Ari (BERKALA FISIKA, 2011)
The linear least square Inversion have been made with matlab8 for a case study of layered ball with the aim to study the response of the gravitational field of a layered ball.The gravitational field of layered ball formulation described later the value is calculated by programming in matlab. As the validation data is computed on the surface of the earth'sgravitational field with a case of six layers with different density and radius. The value aresuitable to the real slate. After the results are appropriate, the results of programming was made is used to calculate the gravitation field of another layered ball object, the data is then used assynthetic data (considered as a data field) which is an inversion of input data on the program aremade.The results obtained in this modeling can be concluded that there are ambiguity from theinversion results, which means that the parameters which be obtained from the invertion methodare very different to the riil parameter if not given early predictive value as the limit of theexpected value. By providing a limit value (the value of the initial estimate) the expected results ofthe inverse can provide results that correspond (nearly) true value.Key words: Inversion, Linier leastquare, layered ball